Light and electron microscopical studies of focal glomerular sclerosis. Issue 9 (December 1971) - Nagi, A. H.; Alexander, F.; Lannigan, R.
Abstract : Renal biopsy material from seven cases of the nephrotic syndrome due to focal glomerular sclerosis has been studied by light, electron, and immunofluorescent microscopy. The nature of glomerular basement membrane changes and the scar tissue was also studied. It was found that the glomerular basement membrane and mesangial matrix formed the major components of scar tissue. On the basis of a short history in some of our cases, a poor response to steroid therapy in the early stages, and the distinct morphological changes, it is suggested that focal glomerular sclerosis has an independent origin and is not a stage of minimal change lesion.